On the Cultural and Social Values of the Chinese Epic Opera "The Long March" (Journal of Namibian Studies : History Politics Culture, 2023)
As an integrated art form, opera originated in Italy and has been introduced to China for more than 100 years. The art of opera has taken root in China and it has been combined with the local musical style of the Chinese people to create a unique genre of national opera with Chinese characteristics. Since the beginning of the 21st century, Chinese opera has once again stepped into a golden age of development, and many excellent opera works have been produced.This paper selects the large epic opera "The Long March," which has been newly composed in recent years and is representative of the new era, as the research object. It adopts the methods of documentary research, interview, logical analysis and empirical summary to analyze and investigate the musical composition and social influence of the opera "The Long March." In this way, it summarizes the cultural and social values of the opera, and extends the discussion on the influence of the opera on the creation of Chinese opera in the new era. The topic and research perspective of this paper are innovative and of significant academic and research implications, and also have strong practical and realistic implications. It is expected that the discussion of the value of this work will provide a theoretical reference for other researchers in this field.